DIVERSITY AND MORPHOLOGY OF ORNAMENTAL PLANTS IN KARO REGENCY: BOTANICAL INVENTORY AND SUSTAINABLE USE POTENTIAL - Wina Dyah Puspita Sari; Aswarina Nasution; Cicik Suriani; Nadia Mubarokah; Anita Kairani (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
This study aims to document the diversity and morphological traits of ornamental plants in Karo Regency and assess their potential for sustainable use. Employing a qualitative descriptive approach, field surveys at Brastagi were conducted at 8 days, morphological observations, and semi-structured interviews with local communities and experts were held with 10 keys conducted. Sixteen ornamental species from 12 families were identified, including terrestrial and epiphytic orchids, ferns, and flowering plants such as Begonia laruei and Ixora javanica. These species are found at elevations of 920–1,000 meters within montane tropical rainforest habitats characterized by high humidity and limited light. Morphological adaptations indicate resilience to these specific conditions. Production data indicate the important economic role of ornamental plant cultivation in Karo Regency. Chrysanthemum, rose, and tuberose are the most widely cultivated species. This reflects their socioeconomic relevance. The integration of botanical and ethnobotanical data provides essential baseline information supporting biodiversity conservation and sustainable horticulture development. This research contributes valuable insights supporting conservation planning and community-based sustainable development in North Sumatra.